2009
DOI: 10.1194/jlr.m800509-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of microRNAs in mouse liver under aberrant energy metabolic status

Abstract: Abbreviations: FDR, false discovery rate; miRNA, microRNA; NAFLD, nonalcoholic fatty liver disease; qRT-PCR, quantitative reverse transcription polymerase chain reaction; SAM, signifi cance analysis of microarray; STZ, streptozotocin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
119
2
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(139 citation statements)
references
References 57 publications
12
119
2
6
Order By: Relevance
“…For example, the expression of miR-122 may be either downregulated in humans and mice, or upregulated in rats. [26][27][28] All these findings confirm a connection between definite miRNA signatures and pathogenesis of NAFLD, but also suggest that further investigations are required.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…For example, the expression of miR-122 may be either downregulated in humans and mice, or upregulated in rats. [26][27][28] All these findings confirm a connection between definite miRNA signatures and pathogenesis of NAFLD, but also suggest that further investigations are required.…”
supporting
confidence: 56%
“…In keeping with a previous published study, we confirmed the downregulation of miR-122. 26 In liver, miR-122 regulates several targets affecting lipid homeostasis, including fatty acid synthase, 3-hydroxy-3-methyl-glutarylcoenzyme A reductase and their transcriptional activators, the sterolresponse-element binding protein-1c and 2. Therefore, miR-122 downregulation may have a significant role in the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, miR-200a is decreased in the kidney of non-obese diabetic apoE KO mice (Wang et al 2011) and in the liver of spontaneous diabetic non-obese GK rats (Herrera et al 2010). Interestingly, miR-200a is increased in liver of obese diabetic ob/ob mice (Li et al 2009) as well as in liver and pancreatic islets of obese diabetes-resistant B6-ob mice (Zhao et al 2009). These findings indicate that the expression of miR-200a is decreased with diabetes but is increased in cases of obesity or when diabetes is associated with obesity.…”
Section: Figurementioning
confidence: 99%
“…miR-122, the most abundant miRNA in the liver, has been reported to mainly affect lipid metabolism by regulating the expression of SREBP-1c, Fas and HMG-CoA (34)(35)(36). Indeed, downregulation of miR-122 was observed in the livers of ob/ob mice, a well-established hyperglycemic model of NAFLD, and in human NASH patients (20,37). Thus, miR-122, a key regulator of cholesterol and fatty-acid metabolism, may be an attractive therapeutic target for metabolic diseases, including NASH.…”
mentioning
confidence: 99%